Populism Is Always Gendered and Dangerous - Mostov, Julie (Frontiers in Sociology, 2021)
This article argues that populism is always gendered and dangerous to women and democracy. The distinctive reliance on the polarization of ‘us” and ‘them” in populism draws on nationalist notions of exclusive belonging, the need for closure to protect the “us” from would be infiltrators, and observance of proscribed gendered roles to ensure the continued rule of the majority (race/ethno-nation). The reproduction of the “us” is too crucial to leave unregulated, and gendered bodies are too vulnerable to violation and occupation to go without vigilance, that is, without surveillance and demographic policing. Gendered narratives support the anti-immigration features of populism and its curbs on democratic institutions, both in the service of national recovery and in its identification of potentially disloyal, suspect voices from within the demos.